Community Acquired Chronic Arthritis due to Pseudomonas aeruginosa in a Previously Healthy Pregnant Woman. (9th October 2014) - Yilmaz, Mesut; Arslan, Ferhat; Mert, Ali
Abstract : Septic arthritis caused by Pseudomonas aeruginosa is uncommon in the immunocompetent population, despite its occurrence in younger patients with open injuries and in intravenous drug abusers. Here we report a case of septic arthritis caused by P. aeruginosa . This case is unique for several reasons. First, it is a case of septic arthritis in a pregnant woman with no traditional risk factors reported in the literature including history of prior traumatic events, hospitalisation, or chronic underlying disease. She was suspected of having transient osteoporosis associated with pregnancy to involve both hip joints. Second, this is the first reported case of a community acquired chronic septic arthritis due to P. aeruginosa involving large joints of both upper and lower extremities. The patient was treated successfully with a combination of ceftazidime and amikacin for 4 weeks followed by oral ciprofloxacin 750 mg twice daily for 8 weeks.